The Urgency of Civil Liability Regulation on Distribution Brain Rot Content - Sinaga, Roulinta Yesvery (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Brain rot content is a type of digital content that is absurd, addictive, and has minimal value educative is more rampant on social media platforms. Although no, in a way, directly violates the law, the distribution of Content can cause loss psychological and social, especially for groups like children and adolescents. Positive Indonesian law does not have norms that explicitly arrange or limit the distribution content kind of Content. Purposes of the Research: This research aims to study arrangements not quite enough to answer civil to distribute brain rot content, with the use of a legal approach lawMethods of the Research: This research is a type of normative legal research conducted to examine the urgency of regulating civil liability for the dissemination of brain rot content from a progressive legal perspective. In examining the issue, several approaches are used, namely the statutory approach and the philosophical approachFindings of the Research: With interpreting return draft action to oppose the law in Article 1365 of the Civil Code in a substantive way, the author proposes that digital platform providers and maker content can request not quite enough answer civil if proven negligent control distribution content that is systemic harms the community. Approach law progressive used for open room Updates more laws adaptive to development technology and dynamics social. So, the need for the formation of new norms in law digital civil capable reach forms non-material losses due to excess contemporary digital culture.